Human biology : concepts and current issues - Johnson, Michael D., 1948- (San Francisco : Pearson Benjamin Cummings, 2006)
Award-winning teacher Michael D. Johnson catches your interest immediately by connecting basic biology concepts to real-world issues that are relevant to your life. Through a storytelling approach and extensive online support, Human Biology: Concepts and Current Issues not only demystifies how the human body works but helps you to become a better consumer of health and science information.
Human biology, science, and society -- The chemistry of living things -- Structure and function of cells -- From cells to organ systems -- The skeletal system -- The muscular system -- Blood -- Hear and blood vessels -- The immune system and mechanisms of defense -- The respiratory system : exchange of gases -- The nervous system : integration and control -- Sensory mechanisms -- The endocrine system -- The digestive system and nutrition -- The urinary system -- Reproductive systems -- Cell reproduction and differentiation -- Cancer : uncontrolled cell division and differentiation -- Genetics and inheritance -- DNA technology and genetic engineering -- Development, maturation, aging, and death -- Evolution and the origins of life -- Ecosystems and populations -- Human impacts, biodiversity, and environmental issues.
Includes bibliographical references and index.
Minimum system requirements: Windows 98, NT, 2000, XP; 366 MHz Intel Pentium processor; 64 MB RAM; 1024 x 768 screen resolution; 8x CD-ROM drive; Browser: Internet Explorer 5.0 or higher, Netscape 7.0; Plug-ins: Flash player 6 or higher, Shockwave Player 8, Quicktime 4; Internet Connection: 56K modem minimum for website or Macintosh.
Keywords: Human biology